(untitled) (SAARC Journal of Agriculture, 2020)
Indigenous technical knowledge (ITK) are based on the experiences of the local people being passed on from one generation to next and has been used for management of pest since ancient times. A study was conducted to collect and document the ITK and their application in pest management from indigenous communities in western mid hill of Nepal. A total sample size of seventy-five respondents from the indigenous communities of Magar, Gurung, and Newar in Tanahun, Lamjung and Kaski districts of Nepal were interviewed with a semi structured questionnaire. The study revealed that subsistence farmers and semi commercial farmers usually made the most use of ITK while commercial farmers rarely used such indigenous knowledge. Use of ITK was highest (85%) by the subsistence farmers, followed by semi-commercial farmers (60%), and lowest (10%) by commercial farmers in pest management. The transfer of ITK was mostly found to be through past generations. The indigenous technological knowledge being applied in pest management should be documented, promoted, and encouraged in combination with scientific knowledge among the farming communities. SAARC J. Agri., 18(1): 251-261 (2020)